2017
DOI: 10.1016/j.copsyc.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive contributions to healthy eating and obesity

Abstract: Obesity results from persistent failure by the brain to balance food intake with energy needs, resulting in a state of chronic energy surplus. Although there are many factors that predispose individuals to weight gain and obesity, the current review focuses on two ways eating behavior may be influenced by sensitivity to interoceptive signals of hunger, satiety, and metabolic energy reserves. First, obesity may be related to hypersensitivity to interoceptive signals of hunger, leading to positive alliesthesia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 79 publications
2
58
0
Order By: Relevance
“…In line with models linking interoception and positive alliesthesia (51), there was also a corresponding increase in hunger and 'wanting', but not 'liking' these food items.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In line with models linking interoception and positive alliesthesia (51), there was also a corresponding increase in hunger and 'wanting', but not 'liking' these food items.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, the ventral striatuminsula connectivity was enhanced in those with insulin resistance (54). Such findings have been used to support models of positive alliesthesia (51); that is hypersensitivity to bodily signals (e.g. hunger) increases the incentive value of environmental food cues that restore homeostasis; an effect that may be accentuated in those with poorer glucose tolerance.…”
Section: Discussionmentioning
confidence: 75%
“…They have shown that DIF may foster the tendency to misinterpret the visceral sensations related to hunger and satiety, thus leading to maladaptive eating patterns (Ernst et al, ; Herbert, Herbert, & Pollatos, ; Jenkinson, Taylor, & Laws, ; Kano, Hamaguchi, Itoh, Yanai, & Fukudo, ; Nakao, Barsky, Kumano, & Kuboki, ; Scarpazza, LĂ davas, & di Pellegrino, ). Recent neuroscientific findings suggest that obesity may be associated with hypersensitivity to interoceptive signals of hunger and insensitivity to interoceptive signals of satiety (Simmons & DeVille, ). Awareness of signals of somatic arousal may not help to control emotional responses but also contribute meaningfully to understand how somatic sensations are experienced as emotions.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore argue that subjective sensations relate to one's interoceptive state. "Interoception" is defined as our perception of internal bodily signals, e.g., hunger, pain, heat, satiety, muscular and visceral sensations [23][24][25][26]. It is furthermore suggested that interoception is the basis for subjective feelings, sensations and self-awareness, representing a subjective evaluation of "how I feel" [18,23].…”
Section: Introductionmentioning
confidence: 99%